"Gay-macho", "travesti" ou "bicha pintosa"? - A produção discursiva sobre representações homoeróticas no Jornal Lampião da Esquina (1978-1981) - Pereira, Ronielyssom Cezar Souza (2017)
We sought to analyze the homoerotic representations in Lampião da Esquina, between 1978 and 1981, to understand how the homosexual discourses on homosexuality represented these subjects during the formation of militant homosexual groups in Brazil. The main objective of this work is to interpret the construction of senses and the discursive practices that stressed the male homoerotic representations in the pages of Lampião da Esquina. In addition, we aimed at some secondary and specific guidelines: historicizing Lampião da Esquina; to present the tensions involving the newspaper, its readers and militant homosexual groups; and, finally, to analyze the homoerotic representations that indicated greater divergence in Lampião da Esquina on effeminate practices. For this, we start with the following question: how did the discursive practices in the newspaper deconstruct stereotypes and reconstructed ideal types that encouraged homosexuals to assume their sexuality? As a theoretical reference, we adopt Michel Foucault's reflections on discourse analysis and Judith Butler on the concept of performativity. Methodologically, we start from the historical contextualization and selection of the sources. Next, we analyze, mainly, the sections Opinião and Cartas na Mesa. We conducted a discourse analysis on the sections cited to compose a file about the representation of male homosexuals, in which the analyzed representations appear. Of these representations we highlight those referring to effeminacy, travestilities and masculinities, because we seem to express better the relations of power between the subjects involved in the discursive production observed in the journal.